Impact of earthquakes on adolescent future expectations: Insights from a study in Türkiye - Küçükkelepçe, Osman; Konyalıoğlu, Fatma Sena; Kurt, Osman; Kılıç, Fedli Emre; Öz, Erdoğan (The European Research Journal, 2025)
Objectives: While earthquakes impact the future expectations of entire societies, adolescents bear a hefty burden due to their transitional stage of life and the intricacies of adolescence itself. Our study examined the factors influencing the future expectations of adolescents residing in the region six months after the earthquake. Methods: A face-to-face survey was conducted involving 385 individuals aged 11 to 17 affected by the February 6 earthquake in Turkey. The survey included sociodemographic inquiries, questions regarding earthquake experiences, and the administration of the Future Expectation scale to all participants. Results: Participants who lost their family members, who were trapped under the debris, and whose family members were trapped under the debris had significantly lower future expectations. Moreover, happier individuals, who perceived themselves as healthier and more socialized, had significantly higher future expectations. Female individuals had significantly lower future expectations in all subdimensions of the scale. Lastly, adolescents who changed their career aspirations post-earthquake exhibited higher scores in all subdimensions of the scale compared to those who did not undergo such changes. Conclusions: Adolescents confronted with traumatic events like earthquakes, particularly those who have lost relatives, often experience a negative impact on their future expectations. However, during subsequent phases, adolescents who report happiness, improved health, and increased socialization tend to harbor more positive outlooks for the future. This underscores the significance of implementing psychosocial rehabilitation efforts following earthquakes.